(untitled) (Physical Education, Health and Social Sciences, 2025)
Abstract Needle stick injuries (NSIs) are a significant occupational hazard for nurses, exposing them to bloodborne pathogens such as HIV, hepatitis B, and hepatitis C. This cross-sectional study assessed the knowledge and practices of 91 nurses at District Head Quarter Hospital and Shahida Islam Teaching Hospital Lodhran, revealing that while 65.93% had good knowledge of NSIs, 26.37% had poor knowledge, and 7.70% lacked awareness. Although 74.73% followed safe practices, 15.38% did not adhere to protocols, and underreporting remained prevalent due to fear, lack of awareness, and administrative barriers. The findings highlight the need for enhanced training, stricter safety measures, and institutional support to mitigate NSI risks and improve post-exposure management.